2013
DOI: 10.1002/ana.23982
|View full text |Cite
|
Sign up to set email alerts
|

Eteplirsen for the treatment of Duchenne muscular dystrophy

Abstract: Objective:In prior open-label studies, eteplirsen, a phosphorodiamidate morpholino oligomer, enabled dystrophin production in Duchenne muscular dystrophy (DMD) with genetic mutations amenable to skipping exon 51. The present study used a double-blind placebo-controlled protocol to test eteplirsen's ability to induce dystrophin production and improve distance walked on the 6-minute walk test (6MWT). Methods: DMD boys aged 7 to 13 years, with confirmed deletions correctable by skipping exon 51 and ability to wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
555
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 655 publications
(581 citation statements)
references
References 30 publications
(41 reference statements)
5
555
2
7
Order By: Relevance
“…Eteplirsen has been previously demonstrated to reliably induce the production of functional dystrophin in patients with DMD,1, 10, 11, 12 and in so doing, significantly slowed the rate of progression of this devastating disease as demonstrated here by comparison of longitudinal 6MWT results to untreated, matched historical controls over 36 months. This was evidenced by a slower decline in walking ability in eteplirsen‐treated patients compared to age‐matched historical controls amenable to exon 51 skipping, with a clinically relevant 75m difference by 24 months, and a statistically significant and clinically relevant difference of 151m by 36 months.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Eteplirsen has been previously demonstrated to reliably induce the production of functional dystrophin in patients with DMD,1, 10, 11, 12 and in so doing, significantly slowed the rate of progression of this devastating disease as demonstrated here by comparison of longitudinal 6MWT results to untreated, matched historical controls over 36 months. This was evidenced by a slower decline in walking ability in eteplirsen‐treated patients compared to age‐matched historical controls amenable to exon 51 skipping, with a clinically relevant 75m difference by 24 months, and a statistically significant and clinically relevant difference of 151m by 36 months.…”
Section: Discussionmentioning
confidence: 63%
“…This is supported by the finding that internally deleted dystrophin proteins occur in patients with Becker muscular dystrophy, a dystrophinopathy allelic to DMD, but with a less severe phenotype 9. The ability of eteplirsen to induce expression of dystrophin in DMD patients was demonstrated by an observed increase of dystrophin‐positive fibers in skeletal muscle, observed increases in dystrophin intensity in this1 and other studies,10, 11 and by the observed restoration of the dystroglycan complex, as evidenced by localization of neuronal nitric oxide synthase and B‐dystroglycan to the sarcolemma 12…”
mentioning
confidence: 64%
See 3 more Smart Citations